(untitled) - Wilkinson, Bruce; (1940-...) (U.S.A, 2002)
In this book, you're going to discover that God's son Jesus revealed a direct link between what you do today and what you will experience after you die. Astoundingly, the majority of spiritual seekers around the world -- including millions who follow Jesus -- seem to have missed what He said. Could you be one? If so, your picture of the future is missing about a billion stars. Author Bruce Wilkinson shows you what Jesus said about God's plan to reward you in eternity for what you do for Him today. What you'll discover will unlock the mystery of God's power, plan and will for your life. And you'll begin to live with the unshakable certainty that what you do today matters . forever!
Keywords: Religion -- Christian Theology -- Eschatology